Measurements of the transverse-momentum-dependent cross sections of J/[psi] at mid-rapidity in proton + proton collisions at √s=510 and 500 GeV with the STAR detector - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert (Physical review, 2019)
We present measurements of the differential cross sections of inclusive J/ψ meson production as a function of transverse momentum (pJ/ψT) using the μ+μ− and e+e− decay channels in proton+proton collisions at center-of-mass energies of 510 and 500 GeV, respectively, recorded by the STAR detector at the Relativistic Heavy Ion Collider. The measurement from the μ+μ− channel is for 0<pJ/ψT<9 GeV/c and rapidity range |yJ/ψ|<0.4, and that from the e+e− channel is for 4<pJ/ψT<20 GeV/c and |yJ/ψ|<1.0. The ψ(2S) to J/ψ ratio is also measured for 4<pmesonT<12 GeV/c through the e+e− decay channel. Model calculations, which incorporate different approaches toward the J/ψ production mechanism, are compared with experimental results and show reasonable agreement within uncertainties.